Pengaruh Dukungan Sosial dan Regulasi Emosi terhadap Quarter Life Crisis pada Dewasa Awal - Fadillah, Umi; Rozi, Fahrul (Instructional Development Journal, 2024)
This study aims to determine how social support and emotional regulation affect quarter life crisis in early adults aged 18-40 years. This study uses quantitative research methods. Sampling using accidental sampling technique through google form with 202 participants. The Social Support measuring instrument uses The Multidimensional Scale of Perceived Social Support (MSPSS) by (Zimet et al., 2010) which has been adapted by (Sulistiani & Kristiana, 2022) Emotion regulation measuring instrument using The Emotion Regulation Questionnaire (ERQ) by (Gross & John, 2003)which has been adapted by (Jannah* et al., 2023). Quarter life crisis measurement tool by Afandi (2023). Data processing using Jamovi 2.3 software with multiple linear regression models. The results of hypothesis testing show that: social support has no effect on quarter life crisis, emotional regulation has no effect on quarter life crisis, social support and emotional regulation have no effect on quarter life crisis by 0.754% with an F value of 1.76 (p>0.001). So it can be seen that social support and emotional regulation are not one of the factors that influence quarter life crisis among early adults.